THE INTERACTION STUDY BETWEEN RADIATIONS FROM COMPUTERIZED TOMOGRAPHY WITH BRAIN, CRANIUM AND SKIN OF HUMAN - Sriwongsa, Kittisak; Rimdusit, Tanaboon; Lertlompiyarat, Paramee; Kiinchohawat, Apichaya; Klumklomchit, Punsak (Life Sciences and Environment Journal, 2021)
This work aims to study partial interaction, mass attenuation coefficient, effective atomic number, half value layer and mean free path by focus the absorption and scattering radiation of nervous system. The study of photon interaction at energies 1–10,000 keV by the WinXCOM software program for studying partial interaction, mass attenuation coefficient, effective atomic number, half value layer and mean free path. These data are important parameters for radiologists to analysis and apply for using with computerized tomography. The relationship of mass attenuation coefficient, effective atomic number, half value layer and mean free path of brain, cranium and skin in photon energies ranging 1–10,000 keV found that photon radiation passes through more than skin and cranium, respectively. The results indicated that all three of the organs effectively absorb radiation from nervous system computerized tomography. When analyzed with computed tomography, the absorption of all three of the organs will affect the efficiency and accuracy in measuring the results from computed tomography.